Smart Watering System and Monitoring Using Smartphone Based IoT System on Chili Plants - Tambunan, Josua Cristian; Jefiza, Adlian (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Optimal watering is essential for the growth of chili plants. This study proposes an IoT-based smart watering and monitoring system that uses fuzzy logic to dynamically determine the duration of watering. This system utilizes a DHT22 sensor to measure air temperature and a YL-69 sensor to measure soil moisture. Fuzzy logic is used to map soil temperature and moisture values into appropriate watering durations, considering predetermined rules based on domain knowledge. The automatic and scheduled watering system produced from this study can function well in controlling the duration of watering with an average duration of 4.52 seconds and is able to maintain soil moisture in chili plants with an average of 73.2%, the automatic watering system also shows more effective results in maintaining soil moisture when compared to manual watering. Meanwhile, the IoT monitoring system or monitoring of the Blynk application using a hotspot network in the chili plant environment can function well with an access distance of 20m. This study provides a unique contribution by combining fuzzy logic to dynamically determine the duration of watering, so that it can adapt to changing environmental conditions. This system opens up opportunities for the development of more complex systems, such as integration with pest and disease monitoring systems.